The AI Act and The Agile Safety Plan - Myklebust, Thor; Stålhane, Tor; Vatn, Dorthea Mathilde Kristin (SpringerBriefs in Computer Science, 2025)
This open access book aims to provide the reader with some basic insight into the AI Act (REGULATION (EU) 2024/1689) and its relevance for the development of high-risk AI systems. It covers all aspects relevant in a safety plan that should serve as the foundation for developing future safety cases for AI safety systems. The topics include e.g. the system definition; hardware, software and its lifecycles; stakeholders and organizations; tools, programming languages, and existing software to be integrated; documentation and work products; procurement and subcontracting; and human aspects. The book aims at experts and stakeholders involved in developing high risk systems, both manufacturers and operators. It is also written for everyone having an interest in how the AI Act impacts technology development processes generally. As such, especially start-ups and small and medium-sized enterprises (SMEs) will find this book useful.